Comparative Plasma Exposure of Albendazole after Administration of Rapidly Disintegrating Tablets in Dogs. (25th August 2013) - Castro, Silvina G.; Dib, Alicia; Suarez, Gonzalo; Allemandi, Daniel; Lanusse, Carlos; Sanchez Bruni, Sergio; Palma, Santiago D.
Abstract : The main objectives of this study were (a) to evaluate the in vitro performance of the rapid disintegration tablets as a way to improve the solid dispersions and (b) to study the in vivo pharmacokinetics of the albendazole modified formulation in dogs. Rapid disintegration of tablets seems to be a key factor for efficiency of solid dispersions with regard to improvement of the albendazole bioavailability. The in vivo assays performed on dogs showed a marked increase in drug plasma exposure when albendazole was given in solid dispersions incorporated into rapid disintegration tablets compared with conventional solid dosage form.